The synthesis of orthoesters and their role as delivery systems for lubricant additives - Roy, Charlotte (2020)
Improving the efficiency of vehicles is crucial to reducing the emissions of internal combustion engines and lessen their impact on the environment. Lubricant friction modifiers successfully reduce the frictional losses within vehicles, but their poor durability limits their potential. Utilising an in situ delivery system for friction modifiers could improve their durability and performance. An ideal approach could use [3,3]-sigmatropic rearrangements, driven by heat, to allow for the in situ formation of esters.